(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
As India has witnessed a big economic liberalization over the years in terms of various industries, FDI inflows to the automotive industry have been rising at a rate. In India, the automotive sector is rising by 18 percent per year. In the automotive industry, India’s basic compensation requires advanced technologies, cost-effectiveness and efficient manpower. In addition, along with vehicle testing and RD centers, India has a well-developed and competent Auto Ancillary Industry. The automotive industry in India ranks third in three-wheeler manufacturing and second in two-wheeler manufacturing. In the years to come, the automotive industry has plenty to deliver respect between the two variables Correlation Direct Investment Inflows in India-Opportunities and reimbursement, major aspects of FDI in the automobile industry, Recent FDI Trends in India.